The Role of the Ministry of Law and Human Rights in Addressing E-Commerce Issues That Create Pros and Cons for Business Actors and Consumers - Lumbantoruan, Abram Andriano Samapta; Simamora, Janpatar (Indonesian Journal of Law and Justice, 2025)
E-commerce has become one of the biggest innovations in the modern world of commerce. With the advancement of technology, e-commerce has brought about significant changes in the way business is conducted, allowing consumers to make purchases and transactions online. Although e-commerce offers many benefits, the debate on the pros and cons of e-commerce continues. This paper examines the pros and cons of e-commerce and the role of the Ministry of Law and Human Rights in these electronic transactions. On the pros side, e-commerce allows wider accessibility for consumers, allowing them to make purchases anytime and anywhere. It also provides an opportunity for small and medium-sized businesses to market their products without having to rely on a physical location. On the other hand, there are pros and cons related to the security of online transactions and consumer protection, as well as the impact of e-commerce on brick-and-mortar stores and the environment. This study highlights the fact that e-commerce poses complex pros and cons, the Ministry of Law and Human Rights provides assistance in addressing issues related to this and the many aspects that need to be considered. With this study, it is hoped that we can better understand the implications of e-commerce in everyday life, and find ways to maximize its benefits while minimizing its risks.